Website-Based Digital Wedding Invitation Generator Application - Adi Maulana Triadi; Reyvan Adryan Rohmatulloh; Arief Agus Sukmandhani (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This research aims to answer the problems in making conventional digital invitations at Our invitation. Users can create digital invitations according to their own wishes and designs and can preview the appearance of the invitations instantly. And Admin can add new themes that Users can use. This application is made in the form of a website. The research starts from problem identification and literature study to application development using the waterfall method. The application has passed testing through the user acceptance test, and evaluation is carried out by distributing questionnaires to users with the conclusion that the application meets user needs.